ANALISA PERSPEKTIF ISLAM DAN KOSMOPOLITANISME TERHADAP UPAYA GLOBAL PENANGANAN PENGUNGSI SURIAH - Lunyka Adelina Pertiwi (The Indonesian Islamic Studies and International Relations Association (Insiera), 2016)
The “waning” of inter-state boundaries in contemporary global politics leads the Syrian refugees issue into global concern. However, the global community, including Muslim-Arabic states, Western states, and international organizations are unable to handle and fulfill the needs of Syrian refugees. This article tries to answer of why the global community could not handle the issue of Syrian refugees properly. Both cosmo-politanism and Islamic perspectives respect to the basic human rights, condemn the discriminative actions and negative stereotypes, and condeming everybody who assuming human beings as the other. Islamic perspective does not support for the absence of consultation and discussion in searching for solutions of problems. Based on cosmo-politanism and Islam perspectives, there are two reasons, namely: the unwillingness to understand basic human rights of the refugees, and the absence of consultation and discussion among Muslims and other ethnic groups.